PRACTICES AND MEANINGS AROUND THE SLEEP-WAKE CYCLE IN ELDERLY PEOPLE FROM GREATER SANTIAGO - Castillo Cortés, Marcela; Moya, Mario Ociel (Chilean Journal of Primary Care and Family Health, 2022)
Introduction: the census reports in Chile reflect an advanced demographic transition towards the aging of the population. The sleep/wake process is a relevant dimension in people's lives and research indicates that it changes with age. Objective: to analyze the beliefs and practices of the elderly regarding the sleep/wake cycle, in the communes of La Pintana and Las Condes in the city of Santiago de Chile. Methods: a qualitative study of a phenomenological nature focused on collecting from the stories of the elderly, the experiences related to the sleep/wake process. Seventeen elderly people without cognitive impairment and self-reliant participated voluntarily (eight from La Pintana and nine from Las Condes). Results: there are practices that can increase the changes imposed by aging of the system that supports the sleep-wake cycle. The decrease in hours, the quality of sleep and the need to sleep during the day lead the elderly to take measures in search of a good sleep. The hours of sleep are far from the hours established as adequate to achieve healthy aging. The constant complaints and the discreet education in this aspect create feelings of hopelessness and resignation to continue with the experience of exhausting sleepless nights. Conclusions: knowing the CSV allows to verify the health status and functionality of the elderly, which favors comprehensive prevention measures in Primary Health Care.